Blood Magnesium Levels in Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Serum and erythrocyte magnesium levels were screened between attacks in patients with migraine without aura (n=38) and with aura (n=6) and for comparison, in a group of patients suffering from chronic tension-type headache (n=25) as well as a group of control patients (n=19) at the Headache Unit, Citadelle University of Liege, Liege, Belgium.